Chemical fingerprints of large organic molecules in scanning tunneling microscopy: Imaging adsorbate-substrate coupling of metalloporphyrins - Buchner, Florian; Warnick, Karl-Georg; Wölfle, Thorsten; Görling, Andreas; Steinrück, Hans-Peter; Hieringer, Wolfgang; Marbach, Hubertus (Journal of Physical Chemistry C, 2009)
In this combined experimental and theoretical work we demonstrate at the example of tetraphenylporphyrins on Ag(111) how differences in individual adsorbate orbitals and their interaction with the substrate can be exploited to switch the appearance of the adsorbate in scanning tunneling microscopy (STM) experiments, such that electronically and chemically very similar large molecules become distinguishable in STM. In particular, an intermixed layer consisting of 2HTPP (TPP ) tetraphenylporphyrin), CoTPP, and FeTPP molecules on Ag(111) was investigated, and it is demonstrated that STM images acquired with different bias voltages constitute fingerprints of the different molecules within the intermixed layer. By means of density functional calculations the observed features could be explained in detail and traced back to a direct orbital interaction of the adsorbed molecule with the surface. The explicit consideration of the surface in the calculations therefore turned out to be decisive to achieve good agreement with experiment. © 2009 American Chemical Society.